Analysing the socio-psychological construction of identity among pre-service teachers. Issue 1 (1st January 2017) - Sanya Pelini, Eunice
Abstract: A teacher's representation of self is crucial in how they construct their identity. In this article, it is argued that pre-service teachers' identities are intricately linked to their perceptions of the teaching profession. This paper explores the social construction of identity among pre-service teachers and the implications for professional identity. It focuses on pre-service teachers in Kenya. The findings presented here are primarily based on semi-structured interviews distributed among students enrolled in a Kenyan university. They highlight pre-service teachers' difficulty in overcoming the negative perceptions of the profession and building positive identities of self as teacher. They also underscore the need for training programmes that take perceptions and representations of the teaching profession into account when formulating training curricula.